PENGARUH KARAKTERISTIK INDIVIDU DAN KARAKTERISTIK PEKERJAAN TERHADAP MOTIVASI KERJA SERTA DAMPAKNYA TERHADAP KEPUASAN KERJA (Studi Pada Karyawan Dinas Pertanian Dan Kehutanan Kabupaten Rembang) (Jurnal Mahasiswa Pasca Sarjana, 2015)
The issue of job satisfaction depends on three main components of the individual as the executor of the work, the work performed, and the organization where the individual worked. Therefore the characteristics of each component must be considered to create job satisfaction. Characteristics of the work are the nature of the duties which include responsibility, task variety and level of satisfaction derived from the work itself. The work is intrinsically satisfying and more motivating for most people than work is not satisfactory. Every person has the vision, goals, needs and abilities are different from each other. This difference will be brought in the world of work, which will lead to satisfaction with one another differently, despite working the same place. The purpose of this research is to analysis the effect characteristic of the individual and job characteristics on job satisfaction with work motivation as mediator on employof Dinas Pertanian dan Kehutanan Kabupaten Rembang. The method used is the census with a population of 103 person. Data was collected by questionnaire to be filled directly. The results indicate that individual characteristics, job characteristics and motivations significant positive effect on job satisfaction. Direct influence of individual characteristics on job satisfaction is stronger than the indirect effect of individual characteristics on job satisfaction through a motivation, or in other words, mediation is less powerful than the direct effect of individual characteristics on job satisfaction. The direct effect of job characteristics on job satisfaction is stronger than the indirect effect of job characteristics on job satisfaction through a motivation, or in other words, mediation is less robust than the direct influence of job characteristics on job satisfaction. Key words: Individual Characteristics, Job Characteristics, Job Satisfaction, Work